Contemporary Ecopedagogical-Political Dialectics Based on Paulo Freire’s Philosophy in Palangka Raya, Indonesia - Munte, Alfonso (Journal of Education for Sustainability and Diversity, 2022)
Paulo Freire’s philosophy is still universally relevant and discussed almost all over the world, including in Indonesia. The philosophy is dialectical in the holistic context of education, covering active awareness, pedagogical imperatives, skepticism, and domination of the social environment. This article focuses on the topic of Freire’s philosophy in the context of students in Palangka Raya as subjects. In this study, the researcher found several responses from the subjects when discussing active awareness and pedagogical imperatives. The first subject raised both skepticism and appreciation. The dialectical behavior of the educational journey led to a paradoxical attitude. The second subject struggled to see awareness as something that must be collective. Then, the next subject narrated ecopedagogy through his origins and the place where he was studying. To be noted, the researcher conducted a qualitative study using in-depth interviews with several students who were currently studying in Central Kalimantan Province, Indonesia.